2018
DOI: 10.3390/jcm7110399
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial Cyst: Never Too Late to Diagnose

Abstract: Pericardial cysts are uncommon benign lesions of the middle mediastinum, making up less than 6% of all mediastinal masses. They are often detected as incidental findings on chest imaging and some can resolve spontaneously. Rarely, however, they may cause symptoms of chest pain, right ventricular outflow obstruction, and persistent cough. Furthermore, they may affect cardiac tamponade after acute rupture or cyst haemorrhage resulting in sudden death. We report the case of a 102-year-old woman presenting with ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Congenital PCs and diverticula display similar developmental origin, the cystic lesions being considered a remnant of a diverticulum, while acquired inflammatory cysts occur due to a loculated pericardial effusion [ 1 ]. Moreover, different studies suggested that PCs are always connected with the pericardium, although a visible tube-like structure between them is described only in 5% of cases [ 8 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Congenital PCs and diverticula display similar developmental origin, the cystic lesions being considered a remnant of a diverticulum, while acquired inflammatory cysts occur due to a loculated pericardial effusion [ 1 ]. Moreover, different studies suggested that PCs are always connected with the pericardium, although a visible tube-like structure between them is described only in 5% of cases [ 8 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…These are primarily congenital anomalies, with an estimated incidence of 1:100 000 persons, which occur because of the incomplete separation of the pericardial coelom after the third week of gestation [ 2 , 6 , 7 , 8 ]. However, inflammatory cysts may also occur in the context of tuberculosis, echinococcosis, rheumatic pericarditis, trauma, including cardiothoracic surgery, or in patients on chronic hemodialysis, in exceptional cases [ 5 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1,2] Pericardial cysts are caused by incomplete fusion of pericardial mesenchymal Spaces in the embryo and consist of a thin layer of fibrous tissue lined with a single layer of mesothelial cells. [3] On echocardiography, pericardial cysts appear as single or multilocular cystic anechoic structures with thin walls and no obvious blood flow signal. They are most common in the right costophrenic Angle, followed by the left costophrenic Angle, and rarely located in other parts of the mediastinum.…”
Section: Discussionmentioning
confidence: 99%